2014
DOI: 10.1007/s10964-013-0089-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dating Violence Among Sexual Minority Youth: Variation Across Gender, Sexual Minority Identity and Gender of Sexual Partners

Abstract: Dating violence during adolescence negatively influences concurrent psychosocial functioning, and has been linked with an increased likelihood of later intimate partner violence. Identifying who is most vulnerable for this negative outcome can inform the development of intervention practices addressing this problem. The two goals of this study were to assess variations in the prevalence of dating violence across different measures of sexual minority status (e.g., sexual minority identity or same-sex sexual beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
121
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 62 publications
29
121
2
4
Order By: Relevance
“…Furthermore, in a sample of 521 youth sampled at a LGB rally, Freedner, Freed, Yang, and Austin (2002) found that bisexual boys reported higher rates of any type of DV victimization than heterosexual boys, and bisexual girls reported higher rates of sexual DV victimization than heterosexual girls. In the only known DV study to include male and female youth questioning their sexual orientation, Martin-Storey (2015) found that questioning boys were more likely to report DV victimization than bisexual boys, whereas questioning girls reported lower rates of DV victimization than lesbian and bisexual girls. Although these preliminary studies add to our understanding of variability in rates of DV among LGBQ youth, further research is needed, especially research that includes large samples of youth and a comprehensive assessment of sexual orientation, inclusive of questioning youth.…”
mentioning
confidence: 94%
“…Furthermore, in a sample of 521 youth sampled at a LGB rally, Freedner, Freed, Yang, and Austin (2002) found that bisexual boys reported higher rates of any type of DV victimization than heterosexual boys, and bisexual girls reported higher rates of sexual DV victimization than heterosexual girls. In the only known DV study to include male and female youth questioning their sexual orientation, Martin-Storey (2015) found that questioning boys were more likely to report DV victimization than bisexual boys, whereas questioning girls reported lower rates of DV victimization than lesbian and bisexual girls. Although these preliminary studies add to our understanding of variability in rates of DV among LGBQ youth, further research is needed, especially research that includes large samples of youth and a comprehensive assessment of sexual orientation, inclusive of questioning youth.…”
mentioning
confidence: 94%
“…Especially, they found that the odds of suffering IVP if they were lesbian or bisexual females were 76% more than in gay men. Another study also found a higher rate of physical and sexual IPV in LB when compared to gay men 37 . Authors such as Miller et al 35 have suggested that the obstacles that have hindered the recognition of IPV in LB women are ingrained in gender norms because programs and policies have been created by focusing on heterosexual women and they have neglected the people outside that category.…”
Section: Key Topics In Hiv Prevention For Lb Womenmentioning
confidence: 84%
“…We located a single study which addressed adolescent same-sex IPVA experiences and substance use. Martin-Storey (2015) found that binge drinking was associated with IPVA in female same-sex relationships, whereas for boys this was only significant for those who reported an uncertain sexuality status.…”
Section: Substance Use/misuse (Alcohol; Illicit Drugs)mentioning
confidence: 84%
“…Although both showed significant variations in rates across studies: from 1% to 61% in Wincentak et al's review. Studies which include same-sex adolescent relationships indicate that rates are similar, although some forms of abuse such as forced 'outing' are specific to this group (Martin-Storey, 2015, Goodenow and Meer, 2013, Barter et al, 2009a, Halpern et al, 2004. Stonard et al (2015) conclude that IPVA represents a significant problem and that gender is only a factor for sexual violence victimisation.…”
Section: The Extent Of Adolescent Ipvamentioning
confidence: 99%